IMPULSE BUYING IN AN ISLAMIC ECONOMIC PERSPECTIVE: AN ANALYSIS OF FOMO AND DOUBLE-DATE PROMOTIONS ON E-COMMERCE USERS - Fikriyah, Khusnul; Suryaningsih, Sri Abidah; Adabi, Muhammad Akmal Chesta (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
The development of e-commerce in Indonesia has driven significant changes in consumer behavior, one of which is the emergence of the impulse buying phenomenon. This study aims to analyze the influence of fear of missing out (FOMO) and double-date promotions on impulse buying by e-commerce users from an Islamic economic perspective. The research method used a quantitative approach with a purposive sampling technique on 468 respondents who had shopped on online shopping applications. Data analysis was conducted using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results showed that both FOMO and double-date promotions had a positive and significant effect on impulse buying, with double-date promotions being the most dominant factor. This finding confirms that event-based promotional strategies are more powerful in driving consumptive behavior than psychological factors. From an Islamic economic perspective, this type of consumption behavior can conflict with the principles of qana'ah (consumption of wealth), the prohibition of israf (israf), and tabdzir (indulgence in spending). Therefore, Islamic consumption literacy is needed to develop wise and sharia-compliant shopping behavior. For the e-commerce industry, this finding confirms that event-based promotional strategies such as double-date promotions are very effective in increasing transactions. However, companies also need to consider sustainability and ethical aspects to avoid encouraging excessive consumer behavior that could harm consumers. For consumers, this research raises awareness to be more critical and rational in approaching digital promotional strategies, enabling them to distinguish between immediate needs and desires.   Keywords: Impulse Buying, FOMO, Double Date Promo, E-Commerce, Islamic Economy